The Integrity of General Elections Based on Prophetic Journalism - Abdul Hakam Sholahuddin; Iffatin Nur; Akhmad Rizqon Khamami (World Journal of Islamic Learning and Teaching, 2025)
This study examines the integrity of general elections through the lens of prophetic journalism. A qualitative approach was employed to explore the perspectives and experiences of institutional administrators, community leaders, and local residents regarding electoral integrity grounded in prophetic journalism. This approach emphasizes the importance of relationships among various actors in the public policy process, including government institutions, non-governmental organizations, and the private sector. The research was conducted at the East Java Provincial General Election Commission (KPU), with data collected directly by the researcher through observation of words and actions. Data collection was carried out holistically and integratively, focusing on relevance to the study objectives. Data analysis involved systematically searching, organizing, and processing all interview transcripts while ensuring validity through careful verification procedures. The results indicate that electoral integrity can be maintained effectively through a combination of deliberative democracy and prophetic journalism. In this context, the media functions not only as an information distributor but also as a moral agent ensuring transparency, accountability, and fairness throughout the electoral process. Campaigns to validate and counter hoax news during elections are most effective when prophetic journalism is integrated with agenda-setting theory, allowing the media to shape public perception through information filtering, digital literacy education, and the delivery of objective and ethical reporting. Prophetic journalism also serves as a social control mechanism, reinforcing transparency and oversight by combining the press’s watchdog function with principles of honesty, responsibility, and wisdom, preventing electoral manipulation and safeguarding democratic integrity.